Mesothelin-Associated Anti-Senescence Through P53 in Pancreatic Ductal Adenocarcinoma - Liu, Dongliang; Lu, Jianming; Chen, Changyi; Yao, Qizhi (Cancers, 2025)
Objectives: Mesothelin (MSLN) is overexpressed in pancreatic ductal adenocarcinoma (PDAC), promoting cell proliferation, migration, and inhibiting apoptosis. While its oncogenic properties have been documented, the role of MSLN in regulating cellular senescence—a tumor-suppressive mechanism—has remained unexplored. This study is the first to identify and characterize a novel mesothelin-associated anti-senescence (MAAS) effect in PDAC. Methods: A proteogenomic analysis of PDAC tissue samples from the Clinical Proteomic Tumor Analysis Consortium (CPTAC) was performed to evaluate MSLN-associated senescence pathways using WebGestalt. Human and murine PDAC cell lines with modified MSLN expression were analyzed for senescence phenotypes via SA-β-gal staining, Western blotting of key regulators (P53, P21waf1, and P16ink4a), γH2AX immunoblotting, and IL-8 quantification using ELISA. Results: The CPTAC analysis revealed an inverse correlation between MSLN expression and DNA damage/repair pathways. MSLN-deficient cells exhibited classic senescence features—growth arrest, an enlarged morphology, and elevated SA-β-gal activity. The expression of P53, P21waf1, and P16ink4a was upregulated, alongside increased γH2AX levels, indicating the activation of the DNA damage response. IL-8 secretion was significantly higher in the MSLN knockdown cells and reduced in the MSLN-overexpressing cells, consistent with the modulation of the SASP. Notably, MSLN deficiency impaired cell viability without inducing overt cytotoxicity, supporting a shift toward senescence. Conclusions: Our findings uncover a previously unrecognized mechanism through which MSLN promotes tumor progression by suppressing senescence via P53-associated pathways. Targeting the MAAS pathway may offer a novel therapeutic strategy to restore tumor-suppressive senescence and enhance treatment efficacy in PDAC.